Nerve Growth Factor, Brain-Derived Neurotrophic Factor and Osteocalcin Gene Relationship in Energy Regulation, Bone Homeostasis and Reproductive Organs Analyzed by mRNA Quantitative Evaluation and Linear Correlation Analysis - Camerino, Claudia; Conte, Elena; Cannone, Maria; Caloiero, Roberta; Fonzino, Adriano; Tricarico, Domenico (Frontiers in Physiology, 2016)
Nerve Growth Factor (NGF) / Brain-derived Neurotrophic Factor (BDNF) and osteocalcin share common effects regulating energy, bone mass, reproduction and neuronal functions. To investigate on the gene-relationship between NGF, BDNF and Osteocalcin we compared by RT-PCR the transcript levels of Ngf, Bdnf and Osteocalcin as well as of their receptors p75NTR/NTRK1, NTRK2 and Gprc6a in brain, bone, white/brown adipose tissue (WAT/BAT) and reproductive organs of 3 months old female and male mice. Brain and bone were used as positive controls for NGF/BDNF and Osteocalcin respectively. The role of oxitocin(Oxt) and its receptor(Oxtr) was also investigated. Ngf expression shows an opposite trend compared to Bdnf. Ngf/p75NTR expression is 50% higher in BAT than brain, in both genders, but lower in bone. In contrast, Bdnf expression in bone is higher than in brain, but low in BAT/WAT. We found Osteocalcin gene expressed in brain in both genders, but Gprc6a expression is low in brain and BAT/WAT. As expected, Gprc6a gene is expressed in bone. Oxt gene was markedly expressed in brain, Oxtr in the ovaries and in fat and bone in both genders. Ngf is highly expressed in reproductive tissues and p75NTR mRNA levels are respectively 300%, 100% and 50% higher in testis/ovaries/uterus than in brain. In contrast, BDNF genes are not expressed in reproductive tissues. As expected, Gprc6a is expressed in testis but not in the ovaries/uterus. A significant correlation was found between the expression levels of the gene ligands and their receptors in brain, BAT and testis suggesting a common pathway of different genes in these tissues in either male and female. Changes in the expression levels of osteocalcin, Ngf or Bdnf genes may mutually affect the expression levels of the others. Moreover, it may be possible that different ligands may operate through different receptor subtypes. Oxt and Oxtr failed to show significant correlation. The up-regulation of Ngf/p75NTR in BAT is consistent with NGF as an energy regulator and with BDNF regulating bone.